Theoretical approach on characterizing structural and mechanical properties of industrial alloys - Ramadhan, Muhammad Redo; Khansa, Salwa Anindhita; Zulindra, Qoriana; Amalia, Dwi; Astuti, Fahmi (Journal of Metallurgical Engineering and Processing Technology, 2024)
With the goal of entering Indonesia’s golden dream 2045 in mineral technology and utilizations, expansive researches covering both experimental and theoretical aspects are urgently required. Here, we provide theoretical study on structural and mechanical properties of various nickel-based alloys based on first-principles, density functional theory (DFT) technique. First, we evaluate the accuracy of several exchange-correlation functionals (LDA-PZ, GGA-PBE, GGA-PBEsol) by comparing the calculated lattice constants for each system with the known experimental results. Based on the best functional, we analyze structural changes caused by the mixture of different atom to the principal element of nickel. Finally, we derived the related mechanical properties for all systems based on the calculated elastic constants. Furthermore, the elastic constants can also be used to predict the stability of alloy structure.